The Mediating Role of Cognitive Processes in the Relationship Between Peer Victimization and Dysregulated Behaviors in Individuals With Bipolar Disorder - Zarei Goonyani, Akram; Mansouri, Ahmad; Ahi, Qasem; Bahreinian, Seyed Abdolmajid; Saied, Fahime (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective:  The primary objective of this study was to examine the mediating role of cognitive processes in the relationship between peer victimization and dysregulated behaviors in individuals with bipolar disorder.Methods and Materials: This descriptive, correlational study included all individuals with bipolar disorder hospitalized at Razi Psychiatric Hospital in 2023-2024. From this population, 200 individuals were selected using convenience sampling. Data collection tools included the Binge Eating Severity Scale, the Deliberate and Conscious Self-Harm Inventory, the Alcohol Use Disorders Identification Test, the Multidimensional Peer Victimization Scale, the Cognitive Abilities Questionnaire, the Difficulties in Emotion Regulation Scale–Short Form, the Acceptance and Action Questionnaire, and the Levels of Self-Criticism Scale. Data analysis was conducted using SPSS and LISREL software, along with Pearson correlation methods and structural equation modeling (SEM).Results: The study's findings indicated that cognitive processes (cognitive ability, self-criticism, experiential avoidance, and difficulties in emotion regulation) play a mediating role in the relationship between peer victimization and dysregulated behaviors (alcohol consumption, binge eating, and self-harm) in individuals with bipolar disorder (CFI = 0.97, NNFI = 0.97, IFI = 0.97, GFI = 0.94, RMSEA = 0.056).Conclusion: Based on the results of this study, individuals with bipolar disorder who experience peer victimization engage in dysregulated behaviors mediated by cognitive processes. Therefore, clinical interventions targeting cognitive processes may play a significant role in preventing dysregulated behaviors in this group.